2003
DOI: 10.1007/s10350-004-6665-3
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the Sigmoid Colon Seeding a Chronic Anal Fistula

Abstract: Damaged mucosal sites seem to be vulnerable to tumor cell implantation. We describe a case of exfoliated tumor cells from a sigmoid colon cancer seeding a long-standing anal fistula. The implications of this finding are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
(4 reference statements)
0
12
0
Order By: Relevance
“…Notable mammalian studies by Yu and Cohn , Broyn and Hubens et al . have been heavily referenced in modern publications as providing ‘strong support for the concept of tumour cell implantation in mucosal sites that have been altered or denuded by a variety of factors’ . Having reviewed the original articles, the authors of the present review feel the scientific results of these papers may have been misinterpreted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notable mammalian studies by Yu and Cohn , Broyn and Hubens et al . have been heavily referenced in modern publications as providing ‘strong support for the concept of tumour cell implantation in mucosal sites that have been altered or denuded by a variety of factors’ . Having reviewed the original articles, the authors of the present review feel the scientific results of these papers may have been misinterpreted.…”
Section: Discussionmentioning
confidence: 99%
“…Little attention, however, has been given to quantifying the risk of tumour cell seeding during endoscopic procedures of the large bowel. Notable mammalian studies by Yu and Cohn [73], Broyn [74] and Hubens et al [75] have been heavily referenced in modern publications as providing 'strong support for the concept of tumour cell implantation in mucosal sites that have been altered or denuded by a variety of factors' [37]. Having reviewed the original articles, the authors of the present review feel the scientific results of [73] in 1968 demonstrated no evidence of implantation of cancer cells into normal or damaged colonic mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have indicated that immunohistochemical analysis is critical for confirming a diagnosis of anal metastasis of rectal carcinoma [3, 57]. Cytokeratin (CK) is an epithelial protein, so determination of its presence is helpful for establishing the origin of metastatic carcinoma [8].…”
Section: Discussionmentioning
confidence: 99%
“…Histological differentiation and immunohistochemical staining must show the same characteristic in both tumors. More specifically, immunohistochemistry of CK7 and CK20 remains the examination of choice to distinguish between colonic tumor tissues and tumors originating from the anal glands [16]. Ramalingam et al have previously described that anal glands were strongly immunoreactive to antibodies against CK7 but not to CK20 [28].…”
Section: Discussionmentioning
confidence: 99%